A coesão e a coerência em função da persuasão em texto dissertativo-argumentativo: uma abordagem sistêmico-funcional - Lohrer, Magda Branco (2009)
The aim of this research is to study the compositions written by students trying to get into the Administration course of a private university in Curitiba, Paraná. Some of these students will eventually take my courses Personal Development, which is taught in the first semester, and Interpersonal Development, which is taught in the second. Choosing these compositions instead of the ones written by first year undergraduates of the Administration course has to do with my desire to investigate the quality of the texts produced by students who had finished high school in 2007. By doing so we would be able to answer the following question: what kind of text producer has my college been receiving? The answers provided by this research will generate other questions: how can these students be helped? Hasn t the university mistakenly taken for granted that undergraduate students are proficient text writers? Do these students make spelling mistakes? Does their writing lack coherence? What kind of problems are there in these texts in relation to textual cohesion and discourse coherence in terms of the pragmatic context of argumentative/persuasive interaction between writer and reader? This research is grounded on qualitative methodology, for it aims at investigating the argumentative texts written by the students above mentioned. The theoretical approach we will draw upon is the Systemic Functional Linguistics (SFL), by Halliday (1985, 1994, 2004) and his coworkers. SFL sees language as a social process and it develops a methodology which allows a detailed and systematic description of linguistic patterns. The corpus used in this research is made up of 16 compositions whose quality was seen to be good enough for students to be accepted at the Administration course of the private university where I work